OPTIMASI BIAYA PELAKSANAAN KONSTRUKSI GEDUNG DENGAN PENERAPAN VALUE ENGINEERING (Studi Kasus Proyek Pembangunan Gedung Pelayanan Rsud Sanjiwani Gianyar) - I Wayan Suasira; Kadek Wahyu Gunawan; Ni Putu Ary Yuliadewi; I Gusti Ngurah Eka Partama (Jurnal Teknik Gradien, 2023)
In a building construction project must have been a cost since high. Therefore, it is necessary to re-analyze with dianksan value technique. Value Engineering is used for alternatives or ideas which are for better cost results or lower than the price that has become a limitation with good limitations and quality of work. Value Engineering analysis in this study uses four job plans, among others: information stage, creative stage, analysis stage, and recommendation stage. In the creative stage of this research using alternatives - the best alternatives by replacing concrete repair and formwork. For the application of Value Engineering is applied to the work of Beam Work, Floor Plate Work and Column Work. From this stage, the best alternative used in the construction of RSUD Sanjiwani Gianyar Service Building is alternative IV by using wiremesh correction and 8x use formwork. Thus, resulting in cost savings of IDR. 4,432,339,572.59 or 20.77% from IDR. 21,337,615,447.66. Efficiency of execution time on the work of the structure 31 days. This research can be concluded that the application of Value Engineering in the Construction of RSUD Sanjiwani Gianyar Service Building can reduce the cost of the planned reinforced concrete structure work.